Avaliação da resistência à força cortante de lajes alveolares protendidas em piso misto de altura reduzida por meio de modelagem computacional - Souza, Jefferson Rosa de (2021)
To be a competitive solution as a structural system, since both elements are industrialized, reaching efficiency from a structural and constructive point of view. In a conventional composite floor system, the slabs are supported on the top flange of the steel profile and the composite action between the materials is guaranteed by mechanical connection. In a shallow composite floor system (slim floor), the slabs are supported on the bottom flange of the steel profile, which is incorporated into the height of the slab. In this case, the composite action can be guaranteed by mechanisms of adhesion between the materials, by means of concrete pins, reinforcement bars passed in the web of the steel profile or shear connectors. Slim floor system presents various advantages with respect to the conventional composite floor, such as greater protection of the metal profiles against fire and, especially, a reduction of the beam and slab set height. However, during the design phase, the shear strength of hollow core slabs on flexible supports needs particular attention and caution. In this context, this study aims at investigating the mechanical behavior of slim floors, focusing on the shear strength of hollow core slabs supported on steel profiles, through computational modeling via the Finite Element Method. To calibrate the computational models, test results on physical models available in the literature have been used. Numerical simulations of isolated hollow core slabs supported on rigid support and slim floor systems were compared with experimental test results, and analytical models for prediction of the resistant shear force. The computational models well-reproduced the tests of slim floor systems with hollow core slabs. A parametric analysis was carried out to evaluate the influence of the core filling of the slabs and the variation of flexural stiffness of the steel profile. The results of the parametric analysis indicate that the shear strength is marginally affected by the filling of the cores. In the case of the use of slabs with oblong-shaped openings, the filling can reduce the shear strength of the slab. The influence of support flexibility on the shear strength of the slab was well represented by an analytical model available in the literature, providing better strength prediction than the model recommended in technical bulletins published by fib (International Federation for Structural Concrete).